Preparation and Evaluation of Multipurpose Herbal Mouthwash for Oromucosal Diseases - Algin Yapar, Evren; ŞAHİNER, ASLI; Cagan, Burcin; KARTAL, MURAT; KARTAL, MURAT (My University, 2019)
Due to the many advantages of herbal sources in medication, in this study, it was aimed to prepare and evaluate an herbal mouthwash formulation that can be useful for the treatment of some oromucosal diseases. For this aim, extracts of Thymus vulgaris L. (Lamiaceae), Pelargonium sidoides DC. (Geraniaceae), Glycyrrhiza glabra L. (Leguminosae), Matricaria chamomilla L. (Compositae), Melissa officinalis L. (Lamiaceae) and Laurus nobilis L. (Lauraceae) were used to prepare two different formulations. Physical parameters, pH, density, stability, in vitro antimicrobial activity and in vitro cytotoxicity studies were used for evaluation of formulations. Between the investigated formulations, the formulation that contains extracts of Thymus vulgaris L. (Lamiaceae), Pelargonium si doi des DC. (Geraniaceae), and Glycyrrhiza glabra L. (Leguminosae), showed good antimicrobial activity with acceptable physical characteristics, pH, density, stability and no cytotoxicity on fibroblast cells. It has been promised in order to create an effective and safe herbal oral mouthwash having multipurpose use for oromucosal diseases and further studies will be planned in terms of long-term stability and clinical studies.